Characterising the association of latency with α1-antitrypsin polymerisation using a novel monoclonal antibody. (January 2015) - Tan, Lu; Perez, Juan; Mela, Marianna; Miranda, Elena; Burling, Keith A; Rouhani, Farshid N; DeMeo, Dawn L; Haq, Imran; Irving, James A; Ordóñez, Adriana; Dickens, Jennifer A; Brantly, Mark; et al.
Abstract: α1 -Antitrypsin is primarily synthesised in the liver, circulates to the lung and protects pulmonary tissues from proteolytic damage. The Z mutant (Glu342Lys) undergoes inactivating conformational change and polymerises. Polymers are retained within the hepatocyte endoplasmic reticulum (ER) in homozygous (PiZZ) individuals, predisposing the individuals to hepatic cirrhosis and emphysema. Latency is an analogous process of inactivating, intra-molecular conformational change and may co-occur with polymerisation. However, the relationship between latency and polymerisation remained unexplored in the absence of a suitable probe. We have developed a novel monoclonal antibody specific for latent α1 -antitrypsin and used it in combination with a polymer-specific antibody, to assess the association of both conformers in vitro, in disease and during augmentation therapy. In vitro kinetics analysis showed polymerisation dominated the pathway but latency could be promoted by stabilising monomeric α1 -antitrypsin. Polymers were extensively produced in hepatocytes and a cell line expressing Z α1 -antitrypsin but the latent protein was not detected despite manipulation of the secretory pathway. However, α1 -antitrypsin augmentation therapy contains latent α1 -antitrypsin, as did the plasma of 63/274 PiZZ individuals treated with augmentation therapy but 0/264 who were not receiving this medication ( p < 10 −14 ). We conclude that latent α1 -antitrypsin is a by-product of the polymerisation pathway, that the intracellular folding environment is resistant to formation of the latent conformer but that augmentation therapy introduces latent α1 -antitrypsin into the circulation. A suite of monoclonal antibodies and methodologies developed in this study can characterise α1 -antitrypsin folding and conformational transitions, and screen methods to improve augmentation therapy.